The Effect of Organizational Support, Leadership Style and Work Environment to Employee Performance at KPPBC TMP A Pasuruan - Angga Pradika, Alfian; Harsasi, Meirani; Maharani, Anita (Journal of Economics, Business, and Government Challenges, 2025)
Through this research, our aim is to present the dynamics within factors affecting employee performance in KPPBC TMP A Pasuruan, as public service offices. The research approach is quantitative, and KPPBC TMP A Pasuruan public service office as our study object. The technique to collect data was through questionnaire distribution. The type of data collection is cross-sectional, and all incoming data is analyzed through multiple linear regression analysis techniques. After collecting and analyzing the data, we then discover factors assumed to influence employee performance at KPPBC TMP A Pasuruan are proven, partially and simultaneously. The contribution that can be made from this research is to enrich the literatures that discusses concept and case study of employee performance in public services. The concepts including employee performance, organizational support, leaderships’ style and work environment.